An Efficient Method for the Synthesis of 2-Methylallyl Alkenes by Cross-Coupling Reactions - Tabélé, Clemence; Curti, Christophe; Primas, Nicolas; Kabri, Youssef; Remusat, Vincent; Vanelle, Patrice (Synthesis, 2015)
To obtain aromatic 2-methylallyl derivatives, cross-coupling reactions between 2-methyl-2-propen-1-ol and various boronic acids were studied. Among allylic alcohols described for such cross-coupling reactions, 2-methyl-2-propen-1-ol has a low reactivity. Indeed, this substrate did not react with several boronic acids under the previously described conditions and new reaction conditions were investigated. We describe herein a new protocol with small amounts of palladium and ligand, without any additive solvent and under microwave heating. A subsequent simple distillation process not only leads to the product, but also allows the ‘reagent–solvent’ to be recycled for further cross-coupling reactions, without loss of yield. Scope and limitations were studied. Furthermore, when this easy cross-coupling reaction was extended to a wide range of organoboronic acids, high functional group tolerance was observed and a new series of alkenes was synthesized in good yields.
Keywords: palladium; cross-coupling reactions; methylallyl alkenes; boronic acids; allyl alcohols